Gender-affirming hormonal therapy for transgender and gender-diverse people—A narrative review. (February 2023) - Defreyne, J.; Vander Stichele, Clara; Iwamoto, Sean J.; T'Sjoen, G.
Abstract: As the number of transgender and gender-diverse (TGD) people accessing gender-affirming care increases, the need for healthcare professionals (HCPs) providing gender-affirming hormonal therapy (GAHT) also increases. This chapter provides an overview of the HCPs interested in getting involved in providing GAHT. Highlights: The number of people identifying as transgender and gender-diverse is increasing, which may lead to an increase in the number of people applying for gender-affirming hormonal therapy (GAHT). As stated in the recently updated guidelines by the World Professional Association for Transgender Health (WPATH), Standards of Care (soc) 8, GAHT is proven safe when under the medical supervision of a healthcare professional (HCP). HCPs who want to get involved in gender-affirming endocrine care can consult the guidelines by the WPATH, the European Society for Sexual Medicine, and the Endocrine Society, to assist them in providing optimal GAHT to TGD people. GAHT is proven effective in causing physical changes but also improves TGD people's psychological well-being.